Study of transient heat conduction in 2.5D domains using the boundary element method - Godinho, Luís (2004)
This paper presents the solution for transient heat conduction around a cylindrical irregular inclusion of infinite length, inserted in a homogeneous elastic medium and subjected to heat point sources placed at some point in the host medium. The solution is computed in the frequency domain for a wide range of frequencies and axial wavenumbers, and time series are then obtained by means of (fast) inverse Fourier transforms into space-time.